Visualization of the Image of the Nile: Cultural and Geographical Environment of Nilotic Scenes from the Julio-Claudian Period - Mark Sergeevich Chistalev (Античная древность и средние века, 2022)
This article addresses the problem of the cross-cultural dialogue between Egypt and Rome on the example of the image of the Nile, visually embodied in the Nilotic scenes. The geographical scope of the research is limited to the territory of Italy, since this region most accurately reflected the Roman perception of Egyptian culture and was least dependent on the historical prejudices of inhabitants of other provinces of the Roman Empire. It is emphasized that the particularity of the Nilotic scenes is that they are based not on a set of predetermined illustrations of the daily life of the Egyptians, but on a stylistic image that unites the themes of the Nile Flood. Simultaneously, the Nilotic scenes under study have several common features. First, there always is an image of the water element, which in most cases is quite accurately identified as a river valley. Second, there is a typical Nilotic flora and fauna. Third, images of river vessels often occur: from single reed shuttles to ships with deck superstructures and a crew of several people. Fourth and finally, the inhabitants of the Nile Valley are represented as dwarfs. The conclusion is that the political component, which was supposed to remind of the events of the late first century BC, was embodied in special ways of artistic expression of Egyptian realities, particularly in the appearance of dwarfs in the Nilotic scenes. In certain cases, the political context could also be highlighted with colour, such as in the frescoes from the cubicula of the House of Livia on the Palatine Hill, where the yellow frame symbolizes the Golden Age and the glory of Augustus, recalling his victory over Egypt. Generally, the given research suggests that, from the reign of the Julio-Claudians on, the image of the Nile gradually became involved in the process of transformation of the topoi of the Egyptian civilization into symbols of the new Roman imperial culture. Egypt became a part of the Roman world, and the empire accepted and accommodated cultural diversity of the new province.